TEACHER INTERVENTION STRATEGIES TO DEVELOP STUDENTS' ARGUMENTATION IN SOCIOSCIENTIFIC ISSUES LEARNING IN MULTI-LEVEL CLASSES - Alma'ruf, Jamus; Faizah, Ulinnuha Nur; David, Martinez (Jurnal Pendidikan Matematika dan IPA, 2025)
Scientific argumentation skills are essential skills in 21st-century learning, especially in dealing with complex socioscientific issues. However, the diversity of students' abilities in multilevel classes often poses a challenge in designing inclusive learning. This study explores the role of teacher interventions in developing students' argumentation skills related to socioscientific issues in multilevel classes. Using a case study design with mixed approach methods), this study involved 7th-grade students from public junior high schools and 8th-grade students from religious-based junior high schools in Ponorogo city and involved 2 teachers who taught in their classes. Interventions based on Toulmin's argumentation structure and socioscientific issues were conducted to improve students' abilities in tiered classes. The results showed that although there was no significant increase in students' argumentation understanding based on pre-test and post-test scores, there was a significant increase in students' argumentation levels. Teachers succeeded in creating a supportive learning environment through contextual approaches, group discussions, and scaffolding, which effectively improved students' argumentation skills in tiered classes. Constraints such as time constraints, language barriers, and access to technology were identified as factors that influenced learning outcomes in developing students' argumentation skills. This study emphasizes the importance of planned teacher intervention strategies to support students' argumentation development in tiered classes with varying student ability levels.